Child disruptive behaviour problems, problem perception and help-seeking behaviour - Stadler, Sophia (Department of Social Development, 2018)
Disruptive behaviour problems in early childhood are found to be associated with many negative long-term outcomes, such as antisocial behaviour, adolescent delinquency, and substance abuse (Kellam, Werthamer-Larsson & Dolan (1991), as cited in Butler, 2005:1). Even after adolescence this arises, for, as Vogel (2008:16) states the 'frequency of behavioural problems or challenging behaviour among the youth of today often predicts the size of our future prison population'. These findings clearly highlight the importance of early identification of behavioural problems, adequate preventative intervention (Butler, 2005:1) and the necessity for early intervention to prevent their continuity, since behaviour problems are found to worsen without treatment (Loeber, 1982, cited in Butler, 2005:1). The goal of this study is to gain an understanding of disruptive behaviour in primary school learners. To achieve this goal, the objectives of this are to explore the nature of child disruptive behaviour problems; to explore parents and teachers' problem perception of child disruptive behaviour; to explore the problem threshold of parents and teachers toward child disruptive behaviour; and to explore their help-seeking behaviour. The study's aim, therefore, is to better understand and gain more insight in child disruptive behaviour problems before a threshold is reached by parents and teachers and help is sought from social service professionals. The study uses an exploratory qualitative research design to gain insight into child disruptive behaviour problems, problem perceptions and help-seeking behaviour in the Southern Cape Karoo District in the Western Cape. Child disruptive behaviour patterns were analysed along a three-point continuum (from less severe - 'preventative'; to moderate - 'early intervention'; and most severe - 'statutory') based, on problem perceptions of parents, teachers and social service professionals. In addition, the present study examines parents and teachers' problem thresholds to identify help-seeking behaviour and sources. A purposive sampling technique was used to select the participants according to appropriation and availability. Parents and teachers were contacted to participate voluntarily in the research from schools in the area - Acacia Primary School, Baartmansfontein Primary School, Buffelsriver Private Primary School and Matjiesfontein Primary School. The social service professionals who participated consisted of social workers, social auxiliary workers and police officials from the Department of Social Development, Child Welfare SA and the South African Police Service. The study consisted of a broad range of child ages and parental ages. Parent participants also included biological and foster parents. Data was gathered by means of a semi-structured interview schedule administered during 24 individual interviews. The schedule is based on information obtained from the literature review relevant to the models and theories selected. Previous research done by Jessica Hankinson in 2009 in America on child psychopathology, parental problem perception, and help-seeking behaviours was used as a reference for creating the data collection tool, since she also focused on child behavioural problems and used similar models in the theories. This tool was created in such a way as to be relevant to the South African context. The findings confirmed the serious nature of child disruptive behaviour amongst primary school learners, including abusive behaviour, assault, bullying, fighting, swearing, theft, criminal involvement, substance abuse, truancy and school dropouts. The participants were found to be able to perceive their child's problem behaviour and to perceive themselves to be competent parents in dealing with disruptive behaviour. Child disruptive behaviour was found to have a significant effect on classroom learning. Despite legislation banning this, the participants still resort to punitive corrective measures. Stigma related to professional services and the privacy of the family are found to be very relevant in help-seeking efforts. This lead to the conclusion that child disruptive behaviour may become a normal and acceptable phenomenon, and thus leads to late reporting - and social services being contacted only as a last resort. The most important recommendation resulting from the study indicates that there is a need for prevention and early intervention services for child disruptive behaviour. This should address the escalation of the behaviour that later results in the need for statutory services. The study further indicates that various sectors (social workers, teachers, community structures and the departments) need to collaborate and form partnerships in order to enhance the early reporting of children in need and the accessibility and availability of services rendered in rural areas. This could enhance the early identification, reporting and service delivery in order to find problem resolutions.